Genetic diversity of Olive Ridley turtles (Lepidochelys olivacea) in West and North Lombok, Indonesia - AHMAD IZZUL RIFQI ANSORI; AGUS SABDONO; SUBAGIYO SUBAGIYO; NI LUH ASTRIA YUSMALINDA; NI PUTU DIAN PERTIWI; LUH PUTU CANDRA APRILIANI; NI KOMANG ROSSA SRI SAVITRI; ANDRIANUS SEMBIRING (Society for Indonesian Biodiversity, 2026)
Abstract. Ansori AIR, Sabdono A, Subagiyo, Yusmalinda NLA, Pertiwi NPD, Apriliani LPC, Savitri NKRS, Sembiring A. 2026. Genetic diversity of Olive Ridley turtles (Lepidochelys olivacea) in West and North Lombok, Indonesia. Biodiversitas 27 (6): d270618. https://doi.org/10.13057/biodiv/d270618. The Olive Ridley turtle (Lepidochelys olivacea) is a globally distributed species playing a vital ecological role but remains classified as Vulnerable due to anthropogenic threats. This study investigates the genetic diversity and population structure of L. olivacea in West and North Lombok, Indonesia, using mitochondrial control region analysis. Previous genetic studies on this species in Indonesia have been limited to populations in Bali, making this the first report on Lombok populations. As the first genetic study of this species in Lombok, it aims to provide essential data to support evidence-based conservation and sustainable management strategies in the region. A total of 24 tissue samples were collected and analyzed with mitochondrial DNA in the control region (mtDNA CR) amplified using the PCR method, sequencing, and bioinformatic tools including Basic Local Alignment Search Tool (BLAST), Molecular Evolutionary Genetics Analysis version 11 (MEGA11), and DnaSP. All sequences showed high similarity (99.30%-100%) with L. olivacea reference sequences in GenBank. Phylogenetic analysis revealed that all samples clustered within the same global L. olivacea clade, consistent with conspecific classification. However, within this clade, the Lombok population exhibited notably low genetic diversity (Hd = 0.500) and moderate genetic structuring (FST = 0.27390), indicating limited gene flow and potential local isolation. These findings underscore the need for region-based conservation strategies that incorporate genetic data to maintain the adaptive potential and long-term viability of L. olivacea populations in Indonesia.